Factors influencing the occurrence of urinary tract infections in girls aged 14-19 years attending Wera seed secondary school, Wera sub county Amuria district. A cross-sectional study. - Apenyo, Hope; Nansereko, Hasifa; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background Urinary Tract Infections are more common in females due to their shorter urethra, which allows easier entry of bacteria into the urinary system. This study was to assess factors influencing the occurrence of urinary tract infections among girls aged 14 to 19 years attending Wera Seed Secondary School in Wera Sub-County, Amuria District. Methods A descriptive Cross-sectional study design employing a quantitative research method was used to obtain data from a sample size of 40 girls aged 14 to 19 years in a duration of four days, sampled using a simple random sampling technique. A structured questionnaire was used, the data collected was analyzed, and findings were entered into Microsoft Excel 2013, then presented in tables and pie-charts. Results Among the 40 participants sampled, more than half (57.5%) of the respondents were aged 14–15 years, and 62.5% lived in rural areas. On adolescent-related factors, most (77%) always delayed urination due to embarrassment, more than half (55%) used homemade hygiene products, nearly half (45%) wore tight clothes, and most (70%) reported that their parents were not involved in guiding them on proper hygiene practices. Concerning School-related factors, almost all (92.5%) delayed urination due to school rules or activities, and (73%) sometimes had access to clean and private toilets at school. Conclusion The study found that the majority of the girls frequently delayed urination due to embarrassment and used homemade hygiene products. Recommendation There is a need to deploy health workers to regularly sensitize students on proper hygiene and the dangers of reusing sanitary materials or delaying urination.